Familiarity differentially affects right hemisphere contributions to processing metaphors and literals - Lai, Vicky T.; van Dam, Wessel; Conant, Lisa L.; Binder, Jeffrey R.; Desai, Rutvik H. (Frontiers in Human Neuroscience, 2015)
The role of the two hemispheres in processing metaphoric language is controversial. While some studies have reported a special role of the right hemisphere (RH) in processing metaphors, others indicate no difference in laterality relative to literal language. Some studies have found a role of the RH for novel/unfamiliar metaphors, but not conventional/familiar metaphors. It is not clear, however, whether the role of the RH is specific to metaphor novelty, or whether it reflects processing, reinterpretation or reanalysis of novel/unfamiliar language in general. Here we used fMRI to examine the effects of familiarity in both metaphoric and non-metaphoric sentences. A left lateralized network containing the middle and inferior frontal gyri, posterior temporal regions in the left hemisphere (LH), and inferior frontal regions in the RH, was engaged across both metaphoric and non-metaphoric sentences; engagement of this network decreased as familiarity decreased. No region was engaged selectively for greater metaphoric unfamiliarity. An analysis of laterality, however, showed that the contribution of the RH relative to that of LH does increase in a metaphor-specific manner as familiarity decreases. These results show that RH regions, taken by themselves, including commonly reported regions such as the right inferior frontal gyrus, are responsive to increased cognitive demands of processing unfamiliar stimuli, rather than being metaphor-selective. The division of labor between the two hemispheres, however, does shift towards the right for metaphoric processing. The shift results not because the RH contributes more to metaphoric processing. Rather, relative to its contribution for processing literals, the LH contributes less.